Relationship between neuronal migration and cell-substratum adhesion: laminin and merosin promote olfactory neuronal migration but are anti- adhesive (The Rockefeller University Press, 1991)
Regulation by the extracellular matrix (ECM) of migration, motility, and adhesion of olfactory neurons and their precursors was studied in vitro. Neuronal cells of the embryonic olfactory epithelium (OE), which undergo extensive migration in the central nervous system during normal development, were shown to be highly migratory in culture as well. Migration of OE neuronal cells was strongly dependent on substratum- bound ECM molecules, being specifically stimulated and guided by laminin (or the laminin-related molecule merosin) in preference to fibronectin, type I collagen, or type IV collagen. Motility of OE neuronal cells, examined by time-lapse video microscopy, was high on laminin-containing substrata, but negligible on fibronectin substrata. Quantitative assays of adhesion of OE neuronal cells to substrata treated with different ECM molecules demonstrated no correlation, either positive or negative, between the migratory preferences of cells and the strength of cell-substratum adhesion. Moreover, measurements of cell adhesion to substrata containing combinations of ECM proteins revealed that laminin and merosin are anti-adhesive for OE neuronal cells, i.e., cause these cells to adhere poorly to substrata that would otherwise be strongly adhesive. The evidence suggests that the anti- adhesive effect of laminin is not the result of interactions between laminin and other ECM molecules, but rather an effect of laminin on cells, which alters the way in which cells adhere. Consistent with this view, laminin was found to interfere strongly with the formation of focal contacts by OE neuronal cells.